Grazing in a turbulent environment: energy dissipation, encounter rates, and efficacy of feeding currents in Centropages hamatus. - Marrasé, C (1990)
The creation of feeding currents by calanoid copepods increases encounter rates of copepods with their food and provides and advantage in dilute nutritional environments. Small-scale turbulence has also been hypothesized to increase the encounter rate between planktonic predators and their food. Centropages hamatus was exposed to turbulent and nonturbulent environments at two prey concentrations to quantify the influence of turbulence on feeding current efficacy. Turbulent energy dissipation rates used in the experiment were in the range of 0.05-0.15 cm2. sec-3. In the nonturbulent environments, feeding currents increased the encounter rates of C. hamatus 3-5 times that of control encounter areas. In turbulent environments, encounter rates were not increased by feeding currents, yet C. hamatus continued to create feeding currents. Energetic calculations indicate a tradeoff in the value of turbulence to a copepod feeding on phytoplankton. While turbulence is probably beneficial at low food concentrations, it may be deleterious at high food concentrations.